Comparative Overview of Coordination Abilities Development in Primary School Boys - С. В. Жицкий (OVS LLC, 2015)
The research objective is to analyze coordination abilities development in primary school pupils. Research methods: theoretical analysis and collation of scientific and methodological literature, pedagogical testing of coordination abilities, methods of mathematical statistics. The total number of pupils involved in the experiment is 30 children of the first-third grades. Conclusions. Statistically significant changes in indicators of coordination abilities of boys are age-related, according to the results of the tests in "combination of movements of arms, body and legs", "switching from one movement to another", "vestibular stability 1 - option", "static balance by Bondarevsky test". Primary school age is susceptible to development of coordination abilities.